Characterization, antibacterial, antioxidant, antidiabetic, and anti-inflammatory activities of green synthesized silver nanoparticles using Phragmanthera austroarabica A. G. Mill and J. A. Nyberg extract - Khodeer, Dina M.; Nasr, Ali M.; Swidan, Shady A.; Shabayek, Sarah; Khinkar, Roaa M.; Aldurdunji, Mohammed M.; Ramadan, Maryam A.; Badr, Jihan M. (Frontiers in Microbiology, 2023)
Abstract: Diabetes mellitus is a chronic metabolic disorder that exhibited great expansion all over the world. It is becoming an epidemic disease adding a major burden to the health care system, particularly in developing countries. The plant under investigation in the current study Phrag-menthera austroarabica A.G.Mill. & J.A.Nyberg is traditionally used in Saudi Arabia for the treatment of diabetes mellitus. The methanolic extract (200 mg/kg) of the plant and pure gallic acid (40 mg/kg), a major metabolite of the plant, as well as their silver nanoparticle formulae (AgNPs) were evaluated for their antidiabetic activity. The results showed a decrease in body fat, obesity, an improvement in lipid profiles, normalization of hyperglycemia, insulin resistance, and hyper-insulinemia, and an improvement in liver tissue structure and function. However, the results obtained from AgNPs for both extract and the pure gallic acid were the best in most measured parameters. Additionally, the activity of both the crude extract of the plant and its AgNPs were evaluated against a number of gram-positive, gram-negative bacteria and fungi. Although the activity of the crude extract ranged from moderate to weak or even non-active, the AgNPs of the plant extract clearly enhanced the antimicrobial activity. AgNPs of the extract demonstrated re-markable activity, especially against the Gram-negative pathogens P. vulgaris (MIC 2.5 µg/ml) and P. aeruginosa (MIC 5 µg/ml). Furthermore, a promising antimicrobial activity was shown against the Gram-positive pathogen S. mutants (MIC 1.25 µg/ml).